Good Enough Governance: Poverty Reduction and Reform in Developing Countries - MERILEE S. GRINDLE (Governance: An International Journal of Policy, Administration, and Institutions , Vol.17, No. 4, October 2004 (pp. 525-548)., 2004)
The good governance agenda is unrealistically long and growing longer over time. Among the multitude of governance reforms that "must be done" to encourage development and reduce poverty, there is little guidance about what's essential and what's not, what should come first and what should follow, what can be achieved in the short term and what can only be achieved over the longer term, what is feasible and what is not. If more attention is given to sorting out these questions, "good enough governance" may become a more realistic goal for many countries faced with the goal of reducing poverty. Working toward good enough governance means accepting a more nuanced understanding of the evolution of institutions and government capabilities; being explicit about trade-offs and priorities in a world in which all good things cannot be pursued at once; learning about what's working rather than focusing solely on governance gaps; taking the role of government in poverty alleviation seriously; and grounding action in the contextual realities of each country.